HIV/AIDS communication strategies in northern Uganda: development workers opinions on what works - Hasler, Travis (Kansas State University, 2013)
The country of Uganda has an HIV rate of approximately 6.3% countrywide, but in northern Uganda rates have been significantly higher (UNAIDS, 2011). In northern Uganda, a region that has faced decades of war and conflict, 1.2 million people live with HIV. The Extended Parallel Process Model (EPPM) and Social Cognitive Theory (SCT) are used as the theoretical framework in examining how on the ground development practitioners create programming that is the most beneficial in behavior change. Both theories have been used extensively in the design and implementation of HIV/AIDS prevention programs. However, there tends to be little consistency among scholars on what types of behavior change approaches are the most effective, especially in those countries that are most impacted by the AIDS epidemic. The goal of this study was to examine the views of practitioners who work directly with recipients and identify some of the most effective strategies and messages tailored for Northern Uganda based on the EPPM and SCT. A qualitative approach was used in the study. A sample of current, or past long-term (at least two years working in the field) development practitioners from international agencies such as the United States Peace Corps, USAID, International Rescue Committee (IRC), among others. Data were gathered through in-depth interviews, which were conducted online due to geographic constraints of the interviewees, with selected participants currently scattered throughout the United States and sub-Saharan Africa. The study reports practitioners’ views on most effective communication strategies and messages based on experiences while working in northern Uganda. Some of the variables examined include the strategies for changing the belief systems of the population that curb the spread of the AIDS epidemic; self-efficacy strategies; and the nature and level of fear appeal appropriate for the Northern Ugandan situation; and their overall view. Findings of the study indicate respondents feel fear appeal messaging may be ill suited for use in Northern Uganda. Culture-centered approaches may be of best use during the transition from war to reconciliation. Results of the study will help to inform future HIV/AIDS prevention programs on best practices that are both theory and research based.
Keywords: Fear appeals; HIV; Northern Uganda; Development; Mass Communications (0708)